Additional risk of hypertension and smoking for aneurysms in people with a family history of subarachnoid haemorrhage. Issue 5 (15th March 2012) - Rasing, Ingeborg; Nieuwkamp, Dennis J; Algra, Ale; Rinkel, Gabriel J E
Abstract : Background: Smoking and hypertension increase the risk of aneurismal subarachnoid haemorrhage (SAH) two to threefold whereas a familial predisposition increases the risk sixfold. We assessed the additional risk of smoking and hypertension for the presence of an intracranial aneurysm (IA) in first-degree relatives of patients with familial SAH. Methods: We studied first-degree relatives of patients with familial SAH who were screened for the presence of aneurysms. RRs with corresponding 95% CIs for the risk of IA were calculated for smoking and hypertension. Results: The RRs were 1.5 (95% CI 0.7 to 3.2) for smoking, 1.9 (95% CI 1.0 to 3.7) for hypertension and 2.7 (95% CI 1.4 to 5.3) for smoking plus hypertension. The increased RR for hypertension was found in both women and men, but the increased RR for smoking was found in women only. Conclusion: The extent of the increased risk of smoking and hypertension for the presence of IA in first-degree relatives of patients with familial SAH is similar to that in patients without familial predisposition. Risk factor profiles should be included in future genetic studies.